Factors Associated With Influenza Vaccination During Pregnancy: A Real-World Evidence-Based Study - Kuang-Hua Huang PhD; Wan-Ting Xie MS; Jiun-Yi Wang PhD; Te-Feng Yeh PhD; Tung-Han Tsai MHA; Yu-Chia Chang PhD (SAGE Publishing, 2024)
Pregnant women are at increased risk of influenza-related complications. However, the rate of influenza vaccination among pregnant women in Taiwan is low. By analyzing real-world data in this study, we investigated the factors associated with influenza vaccination during pregnancy in Taiwan. This study was a cross-sectional study. We collected real-world data from 2 databases in Taiwan: the Birth Certificate Database and the National Health Insurance Research Database. The study population was pregnant between October 2014 and December 2016 in Taiwan. The multivariate logistic regression was performed to identify factors associated with influenza vaccination, including maternal sociodemographics, trimester, comorbidities, and health-care utilization. The vaccination rate of among pregnant women was 8.2%. Factors significantly associated with a high likelihood of influenza vaccination were age between 30 and 34 years (odds ratio [OR]: 1.14; 95% confidence interval [CI]: 1.10-1.19), second trimester (OR: 1.80; 95% CI: 1.75-1.85), income equal to or exceeding NT$ 38 201 (OR: 1.92; 95% CI: 1.86-1.99), hypertension (OR: 1.16; 95% CI: 1.05-1.29), cardiovascular disease (OR: 1.29; 95% CI: 1.17-1.42), autoimmune disease (OR: 1.47; 95% CI: 1.38-1.58), and chronic pulmonary disease (OR: 1.24; 95% CI: 1.18-1.31). A low level of urbanization, at least 1 hospitalization in the previous year, and the presence of pregnancy complications (eg, gestational diabetes, preeclampsia, and placenta previa) were associated with a lower likelihood rate of influenza vaccination. The influenza vaccination rate among pregnant women in Taiwan was low. Age, gestational age, income level, urbanization level, hypertension, cardiovascular disease, autoimmune disease, chronic pulmonary disease, and pregnancy complications may be associated with influenza vaccination among pregnant women.